2015
DOI: 10.1007/s00277-015-2317-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing pregnancy in chronic myeloid leukaemia

Abstract: Over the past decade, we have witnessed significant advances in knowledge of the biology and treatment of chronic myeloid leukaemia (CML). The development of molecular-targeted therapy with tyrosine kinase inhibitors (TKIs) has fundamentally changed the outcome of this disease. Treatment with TKIs is now the standard of care in patients with CML and has dramatically improved long-term survival in the majority of patients. Patients who achieve major molecular response (MMR) after 2 years of treatment with imati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 43 publications
(45 reference statements)
1
61
0
9
Order By: Relevance
“…166 The safety and efficacy of hormonal agents and targeted therapies have not yet been evaluated in well-controlled studies including pregnant women. [165][166][167][180][181][182] Currently, the use of such agents in pregnant women is not recommended.…”
Section: Management Of Cancer During Pregnancymentioning
confidence: 99%
“…166 The safety and efficacy of hormonal agents and targeted therapies have not yet been evaluated in well-controlled studies including pregnant women. [165][166][167][180][181][182] Currently, the use of such agents in pregnant women is not recommended.…”
Section: Management Of Cancer During Pregnancymentioning
confidence: 99%
“…While not known to be directly mutagenic, the TKIs used to treat CML -while emblematic of the burgeoning field of targeted therapy -are not specific for the mutant BCR-ABL kinase. Off-target inhibition of other tyrosine kinases may impact male and female fertility, spermatogenesis, embryonic implantation, and fetal development [6]. No prospective studies have been or will be completed to assess impact of TKIs on human fertility and/or confirm safety of TKI therapy on spermatogenesis or fetal development.…”
Section: Challenges and Solutions For Patients With CML Desiring Pregmentioning
confidence: 99%
“…Recurrent skeletal malformations as well as abnormalities in the renal, respiratory, and gastrointestinal system have been recorded [10]. Case reports and case series describing pregnancy outcomes in women taking secondgeneration TKIs suggest similar risks [3,6,11,12].…”
Section: Challenges and Solutions For Patients With CML Desiring Pregmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TKIs are contraindicated during pregnancy. Only few investigators have suggested TKI use despite the known teratogenic effects [17,18]. Other therapeutic approaches such as leukapheresis and interferon (IFN)-α can be considered during pregnancy.…”
Section: Hematologic Malignanciesmentioning
confidence: 99%